Legal bases of labor relations in the context of social responsibility - Pankova, Anna (Skhid, 2015)
The article defines and analyzes the main legal principles on which the employment sphere. The problems and obstacles to the formation of the legal principles of labor relations and labor sphere Ukraine in the context of social responsibility and reasonable directions for their establishment and implementation. Focuses on overcoming obstacles irresponsible establishment of the employment relationship to the value of labor and employee value and performance, quality of working life, decent work, sustainable development.